"Degradabilidad ruminal in situ de ensilajes de pasto saboya )Panicum máximun Jacq) con la inclusión de cuatro subproductos agroindustriales". - Acaro Gabriela, Erika Gabriela (2016)
The research was conducted at the Laboratory of Rumiología and Metabolism Nutrition (RUMEN) located at the Experimental Farm "La Maria" State Technical University of Quevedo (UTEQ), aiming at evaluating the in situ ruminal degradability of silage grass Savoie with inclusion of four agroindustrial products. The treatments were: T1 grass Savoie 100%, T2 grass Saboya 85% + pineapple shell 15%, T3 grass Saboya 85% + shell passion fruit 15%, T4 grass Saboya 85% + banana peel 15%, T5 grass Savoy 85% + 15% banana peel. Design Completely Random Block was applied using three cannulated and Brahmin cattle fistulated 500 ± 25 kg average weight. Using the technique of in situ degradability in nylon bags 10 x 20cm, pore size 50 ± 3 um, at incubation times of 0; 3; 6; 12; 24; 48 and 72 hours. As for the in situ dry matter of grass Savoie more the inclusion of four agroindustrial byproducts degradability, statistical differences (p ≤ 0.05) was observed between treatments at different times, evaluating the best treatment T3 (Silage grass Saboya 85% + 15% passion fruit peel) due to its high content of digestible carbohydrates. Showing differences to 0,3,12,48 and 72 hours for DM (Dry Matter), while OM (Organic Matter) showed differences at 12,24,48 and 72 hours, and the MI (Inorganic Matter ) differences at 24, 48 and 72 hours respectively exposed. Key word: Degradability In situ, Waste, peel pineapple, passion fruit peel, banana peel, banana peel, nylon bags